Evaluasi Pemeriksaan MRI Brain dengan Klinis Vertigo di Rumah Sakit Otak dr. Drs. M. Hatta Bukittinggi - Mahfud Edy Widiatmoko; Asumsie Tarigan; Muslimatul Husna (Jurnal Imejing Diagnostik (JImeD), 2024)
Background: Vertigo is a symptom that arises as a result of disturbances in the balance of the vestibular system or disorders of the central nervous system. A radiological examination that can detect clinical vertigo is an MRI examination. There is a difference in the MRI Brain examination protocol for clinical vertigo between theory and the field, namely the addition of the 3D CISS protocol. The aim of this research is to determine the role of adding 3D CISS to MRI Brain examinations in clinical vertigo.Methods: This research is qualitative descriptive research, use 10 patients, and do in January to November 2023. Data was collected by observation, conducting interviews and questionnaires. This research use 13 sequences, namely Axial T2 TSE, DWI, Axial T2 TSE Dark Fluid, T2 SWI, Sagittal T1 TSE, Sagittal T2 TSE FS, Axial T1 TSE, Coronal T2 TSE, Coronal T1 TSE, Axial T1 TSE, Coronal, Sagittal + Contrast with cuts at the upper border of the vertex and the lower border of the cerebellum and T2 3D CISS axial isotropic sequences for the cuts used, namely at the level of the sponge, showing the vestibulocochlear cranial nerve (VIII).Results: The results of the assessment on the T2 3D CISS Axial Isotropic sequence showed that anatomical detail was clearly visible as much as 75% and the spatial resolution was clearly visible as much as 75%.Conclusions: Brain MRI examination with clinical vertigo provides information that helps in understanding the causes of vertigo, allowing for a more accurate and effective treatment approach.